Crosstalk between epithelium, myeloid and innate lymphoid cells during gut homeostasis and disease - Ghilas, Sonia; O’Keefe, Ryan; Mielke, Lisa Anna; Raghu, Dinesh; Buchert, Michael; Ernst, Matthias (Frontiers in Immunology, 2022)
The gut epithelium not only provides a physical barrier to separate a noxious outside from a sterile inside but also allows for highly regulated interactions between bacteria and their products, and components of the immune system. Homeostatic maintenance of an intact epithelial barrier is paramount to health, requiring an intricately regulated and highly adaptive response of various cells of the immune system. Prolonged homeostatic imbalance can result in chronic inflammation, tumorigenesis and inefficient antitumor immune control. Here we provide an update on the role of innate lymphoid cells, macrophages and dendritic cells, which collectively play a critical role in epithelial barrier maintenance and provide an important linkage between the classical innate and adaptive arm of the immune system. These interactions modify the capacity of the gut epithelium to undergo continuous renewal, safeguard against tumor formation and provide feedback to the gut microbiome, which acts as a seminal contributor to cellular homeostasis of the gut.